An unusual Burkholderia gladioli double chain-initiating nonribosomal peptide synthetase assembles 'fungal' icosalide antibiotics. Issue 21 (7th May 2019) - Jenner, Matthew; Jian, Xinyun; Dashti, Yousef; Masschelein, Joleen; Hobson, Christian; Roberts, Douglas M.; Jones, Cerith; Harris, Simon; Parkhill, Julian; Raja, Huzefa A.; Oberlies, Nicholas H.; Pearce, Cedric J.; et al.
Abstract : Fungus-associated Burkholderia gladioli bacteria use a unique 'dual-priming' nonribosomal peptide synthetase to assemble icosalide A1. Abstract : Burkholderia is a multi-talented genus of Gram-negative bacteria, which in recent years has become increasingly recognised as a promising source of bioactive natural products. Metabolite profiling of Burkholderia gladioli BCC0238 showed that it produces the asymmetric lipopeptidiolide antibiotic icosalide A1, originally isolated from a fungus. Comparative bioinformatics analysis of several genome-sequenced B. gladioli isolates identified a gene encoding a nonribosomal peptide synthase (NRPS) with an unusual architecture that was predicted to be responsible for icosalide biosynthesis. Inactivation of this gene in B. gladioli BCC0238 abolished icosalide production. PCR analysis and sequencing of total DNA from the original fungal icosalide A1 producer revealed it has a B. gladioli strain associated with it that harbours an NRPS with an identical architecture to that responsible for icosalide A1 assembly in B. gladioli BCC0238. Sequence analysis of the icosalide NRPS indicated that it contains two chain-initiating condensation (CI ) domains. One of these is appended to the N-terminus of module 1 – a common architecture for NRPSs involved in lipopeptide assembly. The other is embedded in module 3, immediately downstream of a putative chain-elongating condensation domain. Analysis of the reactions catalysed by a tridomain construct from module 3 of the NRPS using intact protein mass spectrometry showed that the embedded CI domain initiates assembly of a second lipopeptide chain, providing key insights into the mechanism for asymmetric diolide assembly.